The BMS Tool Monitoring Vertiv UPS and Vision Lithium-Ion Battery System - Sithole, Tshepo; Veerdhi, Vasudeva Rao; Sithebe, Thembelani (International Journal of Electrical, Energy and Power System Engineering, 2024)
In my previous work published in an acknowledged publication, titled "Factory test of a TP-100 Lithium Ion Vision Battery System for possible Implementation in Soweto, Johannesburg, South Africa," According to the findings from the study report, the TP-100 Vision Lithium-Ion battery system was found to be suitable for implementing a wind turbine system in Soweto. Furthermore, the study's findings indicated that Lithium-Ion batteries were the optimal choice for storing energy in wind turbines. These batteries provided significant total cost of ownership (TCO) reductions over a 10-year period, without the inconvenience and expenses associated with replacing lead-acid batteries. This research paper aims to validate the precision of parameters obtained from the integration of a 160 kVA Vetiv Three Phase UPS to a TP-100 Vision Lithium Ion Battery system in contrast to those obtained from the Battery Monitoring System (BMS) while using Tool BMS Version 1.3 Software. The results validation was evident as the parameters acquired from the UPS and Battery system were found to be accurate when compared to those observed through the BMS tool. Finally, utilizing the Smart Cloud Management System (SCMS), validity was shown by the ability to remotely monitor the operation of both the UPS and the Li-ion Battery system.